2020
DOI: 10.1111/jphd.12402
|View full text |Cite
|
Sign up to set email alerts
|

Understanding value in oral health: the oral health value‐based care symposium

Abstract: Objective: There are both opportunities and challenges with the implementation of oral health value-based care (OHVBC). To tackle concerns and advance conversation, a symposium was convened with subject matter experts to develop a gap analysis and capture insights into professional readiness for value-based care design. Methods: The symposium was convened as a private event for 46 participants over the course of one and a half days in December 2019. Thematic analyses utilized the OHVBC Readiness Framework (Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Analysis revealed 10 specific behaviors that professionals pursued in VBHC, next to acting upon their professional standards ( 68 ). These interconnected and mutually reinforcing behaviors, as visualized in Figure 4 , are to (1) focus on what matters to patients and adopt other VBHC mindsets ( 24 , 31 33 , 47 , 50 , 52 , 53 , 61 , 62 ), (2) measure outcomes ( 14 , 24 , 31 35 , 44 , 56 , 68 ), (3) learn and improve care ( 14 , 24 , 31 34 , 47 , 53 , 62 , 66 , 68 70 ), (4) organize care around the full cycle of disease ( 24 , 32 , 44 , 45 , 54 , 60 , 61 , 64 , 66 , 70 73 ), (5) participate in population health and prevention ( 24 , 62 , 66 , 70 , 72 ), (6) discuss value in the clinical encounter ( 31 , 47 , 50 , 55 , 56 , 58 , 63 , 64 , 74 , 75 ), (7) involve patient representatives ( 24 , 31 33 , 50 ), (8) take accountability for patients and resources ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis revealed 10 specific behaviors that professionals pursued in VBHC, next to acting upon their professional standards ( 68 ). These interconnected and mutually reinforcing behaviors, as visualized in Figure 4 , are to (1) focus on what matters to patients and adopt other VBHC mindsets ( 24 , 31 33 , 47 , 50 , 52 , 53 , 61 , 62 ), (2) measure outcomes ( 14 , 24 , 31 35 , 44 , 56 , 68 ), (3) learn and improve care ( 14 , 24 , 31 34 , 47 , 53 , 62 , 66 , 68 70 ), (4) organize care around the full cycle of disease ( 24 , 32 , 44 , 45 , 54 , 60 , 61 , 64 , 66 , 70 73 ), (5) participate in population health and prevention ( 24 , 62 , 66 , 70 , 72 ), (6) discuss value in the clinical encounter ( 31 , 47 , 50 , 55 , 56 , 58 , 63 , 64 , 74 , 75 ), (7) involve patient representatives ( 24 , 31 33 , 50 ), (8) take accountability for patients and resources ( …”
Section: Resultsmentioning
confidence: 99%
“…Organizational support and legitimacy VBHC resource ( 24) "Even if it was impossible to make use of all the patient representatives' opinions and experiences, participants were proud of their cooperation with the representatives as this contributed to the legitimacy of their implementation work" (24) Environment resource (24,33,48,50,69) "Over time, participants came to understand the importance of the hospital director's unequivocal standpoint that VBHC was to be used as a management tool. This standpoint gave legitimacy to decisions within the teams" (33) Environment demand (24,32,33,35,55,72,76) "Participants felt they had been thrown into the deep end when it came to implementation work" (33) Pride VBHC resource ( 24) "[…] participants were proud of their cooperation with the representatives as this contributed to the legitimacy of their implementation work" (24) complexity with new tasks in VBHC as a result of task expansion (60). The second study suggested information overload due to working with care pathways (73).…”
Section: Task Complexitymentioning
confidence: 99%
“…The results also revealed that dental providers who use telehealth are 34% more familiar with alternative payment models (APMs) and are 45% more likely to have an increased interest in learning about APMs than those who don't use telehealth. With the expected rise of valuebased care and APMs in dentistry 4 , telehealth can be used as a tool to extend care in ways that enhance the financial sustainability of dental practices. Telehealth can reduce the cost of care through efficient and widespread delivery of care and oral health education, while also enhancing the capacity of practices to provide care for additional patients or existing patients with more complex needs.…”
Section: Telehealth and The Future Of Dental Care Financingmentioning
confidence: 99%
“…Oral health values have been closely related to treatment-seeking behaviors, as attending dental appointments, and engaging in preventive oral care because values provide older people with standards for behavior to reach optimum oral haleness based on the perceived magnitude of a certain oral health comportment. Oral health values are wellacquainted as the extent to which one views dental status as important or meaningful, by dedication to improve or maintain one's teeth, gingiva, and other aspects of orofacial functioning" [17] . Regrettably, older people head to drive supplementary attention to treating their systematic comorbidities rather than oral disorders, despite the possibility that, at such life juncture, the oral health troubles are aroused and triggered [18] .…”
Section: Introductionmentioning
confidence: 99%